2016
DOI: 10.1093/epirev/mxv005
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Attitudes, Screening Practices, and Interventions to Reduce Firearm-Related Injury

Abstract: Firearm injury is a leading cause of injury-related morbidity and mortality in the United States. We sought to systematically identify and summarize existing literature on clinical firearm injury prevention screening and interventions. We conducted a systematic search of PubMed, Web of Science, Cumulative Index of Nursing and Allied Health Literature (CINAHL), PsycInfo, and ClinicalTrials.gov for English-language original research (published 1992–2014) on clinical screening methods, patient-level firea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 120 publications
2
116
0
Order By: Relevance
“…Prior work, including the large ED-Safety Assessment and Follow-up Evaluation (ED-SAFE) trial, documents that ED clinicians often do not routinely counsel about lethal means 21,22,3336 and their counseling can be improved. 37 Even with political sensitivities about guns, 38 patients are receptive to receiving guidance, 19,3941 and counseling can improve storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work, including the large ED-Safety Assessment and Follow-up Evaluation (ED-SAFE) trial, documents that ED clinicians often do not routinely counsel about lethal means 21,22,3336 and their counseling can be improved. 37 Even with political sensitivities about guns, 38 patients are receptive to receiving guidance, 19,3941 and counseling can improve storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent systematic review identified no studies of the accuracy or predictive value of screening for firearm access among high-risk patients (5). Such absence of evidence is common.…”
Section: Benefitsmentioning
confidence: 99%
“…We then discuss the circumstances in which prevention efforts might be most appropriate. We briefly review other barriers to their more widespread adoption, patients' opinions about physicians addressing firearms, and the effectiveness of such prevention practices; more extensive information is available elsewhere (5,6). We offer specific recommendations, based on the limited evidence available, for how physicians can incorporate firearm-related injury prevention into the care of their patients.…”
mentioning
confidence: 99%
“…Most research on firearm injury prevention interventions has been conducted outside of the ED. 45 Future work should determine the theoretical basis, format, and demographic tailoring of ED-based interventions to prevent all types of firearm injury, and to reduce harm after an injury or death has occurred. Interventions must then be rigorously developed and tested for efficacy, effectiveness, and disseminability.…”
Section: Cross-cutting Themesmentioning
confidence: 99%